Scoping Review of Kidney Patients and Providers Perspectives on Disaster Management - Elie Fadel; Shreya Udupa; Isabelle Ethier; Alessia N. Paparella; Lindsay Hales; Caroline Stigant; Laura Horowitz; Catherine Weber; Shaifali Sandal (Kidney International Reports)
Introduction: Patients with kidney disease are uniquely vulnerable to disasters and the need to understand stakeholder experiences to improve disaster preparedness has been highlighted. We aimed to explore the existing literature capturing patient and provider perspectives, identify research gaps, and develop research priorities in disaster management. Methods: This was a scoping review of the empirical literature that has explored the lived experience and preparedness of patients, caregivers, or healthcare professionals during natural or human-caused disasters. A content analysis using an inductive approach was conducted. Results: Of the 11,146 titles and abstracts screened, 22 met our inclusion criteria and emerged from Japan (n = 8), USA (n = 8), Syria (n = 2), Turkey (n = 2), China (n = 1), and Europe (n = 1, related to the Russian invasion of Ukraine). The outcomes examined were variable focusing on the following 4 aspects of disaster management: (i) identifying patient-level issues (preparedness, personal challenges, and psychosocial impact); (ii) damage assessment (infrastructure and equipment, personnel, and patient outcomes); (iii) response assessment (hemodialysis treatments delivered or missed, delivery of other kidney replacement therapies, and identifying practice gaps); and (iv) system assessment (examining capabilities and addressing surge capacity). The studies were at risk of survivor bias and most only used an investigator-designed survey for data collection. There was a dearth of evidence capturing the perspectives of caregivers, and pediatric and other vulnerable patients. Conclusion: The literature examining patient and provider perspectives or experiences is scarce and at risk of bias. Methodological, population, outcome, process, and impact priorities are proposed to guide future research initiatives and generate evidence to inform context and disaster-specific relief efforts.